Surface modification of Ti-allloy with silver silicon nitride coating for antibacterial applications / Umi Zalilah Mohamad Zaidi - Umi Zalilah, Mohamad Zaidi (2019)
Ti64 alloys is an alpha-beta titanium alloy with good corrosion resistance, high strength-to-weight ratio, excellent physiochemical stability, mechanical integrity and good biocompatibility. Ti64 alloy is the most promising biomaterials started to replace both stainless steel and cobalt-based alloys in many medical applications such as in orthopedics, dental areas and others. However, Ti64 alloy loses its biocompatibility when it is introduced into human tissues due to possible toxic of Vanadium (V) and Aluminum (Al) release. Releasing of these ions could cause many health problems like Neuropathy, Alzheimer and Osteomalacia. Therefore, to overcome the problem, surface modification using silver silicon nitride film via magnetron sputtering technique was proposed. Silver was proven to have an antibacterial function while silicon nitride is a biocompatible material with low wear rate. The AgSiN thin film is aimed to improve the biocompatibility and mechanical performance of Ti64 alloy by reducing the releasing of V and Al ions caused by debris or wear as well as providing antibacterial properties through the releasing of silver ions in an aqueous environment. Among the deposition parameters such as DC-RF power, temperature, gas flow rate and deposition time, substrate bias is considered as an effective way to control the thin film microstructure and its properties. In this study, a set of experimental depositing AgSiN films on Ti64 alloy using different bias voltage (0, -75, -150 and -200 V) were fabricated. The surface characterization and mechanical performance of the thin film with respect to bias voltage were studied using scanning electron microscope (SEM), atomic force microscope (AFM), X-ray diffraction (XRD), X-ray spectroscopy (XPS), nanoindentation, scratch test and wear test. Crystallite size and microstrain of the films were determined using Approximation Method to further understand the deposited films. Meanwhile, the biological function of the films was tested through wettability and antibacterial tests. According to the results, all thin films showed similar morphology with the highest iv adhesion strength (596 mN) of the AgSiN film was obtained for sample deposited at -75 V. In terms of hardness (5.5 GPa) and elastic modulus (211.0 GPa), sample deposited at -150 V showed an improvement for about 50% compared to the Ti64 substrate (H=2.75, E=113.8). Microstrain values acquired from the Approximation Method were used to project the residual stress present in the film where the lowest compressive residual stress (0.06 GPa) was noted for samples that have highest adhesion strength and highest thickness. In terms of biological functionality, all films showed hydrophilic property with wetting angle observed were below 90º. An inhibition zone area that observed on Bulkholderia pseudomallei (B.Pseudomallei) and Escherichia coli (E.coli) were 7 and 10 mm, respectively which proved the AgSiN films as a promising candidate to be used in antibacterial applications.